A phytochemical study of Morinda roioc L. (Family Rubiaceae) and alkaloids in aged potatoes, Solanum tuberosum L. (Family Solanaceae) - Park, Young Han
Part 1: Twelve anthraquinones, damnacanthal, nordamnacanthal, copareolatin-1 (or 5), 6-dimethyl ether, 2-formyl-3-hydroxyanthraquinone, morindone, soranjidiol, rubiadin-1-methyl ether, lucidin, tectoquinone, copareolatin-6-methyl ether, morindone-5-methyl ether, and soranjidiol-1-methyl ether, and methyl palmitate were isolated from 10% aqueous methanol and sodium carbonate soluble fractions of roots of Morinda roioc. 2-Formyl-3-hydroxyanthraquinone, morindone-5-methyl ether, and soranjidiol-1-methyl ether have been reported for the first time as natural products. Damnacanthal, nordamnacanthal, 2-formyl-3-hydroxyanthraquinone, and lucidin were found to have antibacterial activity against Bacillus subtilis, Staphylococcus aureus, and Mycobacterium smegmatis.
Part II. Two major steroid glycoalkaloids, α-solanine and α-chaconine, were isolated from aged tuber slices of potatoes, Solanum tuberosum L. var. Kennebec. A minor glycoalkaloid was isolated and tentatively identified as β-chaconine on the basis of melting point, specific rotation, and IR spectrum. Nonalkaloidal substances, 4,4'-isopropylidenediphenol and magnesium hydroxide, were isolated also from the crude alkaloid fraction.
Available to the general public.
Thesis (Doctor of Philosophy in Pharmacognosy)--University of Mississippi, May 1977.
Keywords: Plants -- Analysis; Rhubarb; Potatoes